Caregiving in a Global Context - Poulsen, Shruti; Estrada, Diane (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2014)
Abstract The worldwide changes in the economic markets have led to an unprecedented increase in global migration estimated at 214 million (United Nations-International Organization for Migration, 2008). This global migration has increased the number of transnational families worldwide (Dade, 2004) that now face unique physical and psychological challenges for the provision of care for aging adults. Regardless of the precipitating event, global migration has challenged definitions of family, family responsibility, and generational roles (Baldassar, 2008). As the demographics of the world population shift towards a graying era, family therapists need to understand the impact that a changing global economy and economies of kinship have on the lives of family members who migrate and those who are left behind. The goal of this paper is to increase the knowledge base pertaining to transnational families and to make visible the needs of families who provide care across transnational borders.